The role of financial speculation in driving the price of crue oil - Ron Alquist; Olivier Gervais (Bank of Canada, 2011)
Over the past 10 years, financial firms have increased the size of their positions in the oil futures market. At the same time, oil prices have increased dramatically. The conjunction of these developments has led some observers to argue that financial speculation caused the run-up in oil prices. Yet several arguments cast doubt on the validity of this claim. First, although the stock of open futures contracts is many times larger than the flow of oil consumption in the United States, comparing these two statistics is misleading. Stocks are not measured with respect to a specific unit of time but flows are, so the two are not directly comparable. Second, empirical analysis shows that changes in financial firms' positions do not predict oil-price changes, but that oil-price changes predict changes in positions. Third, the evidence indicates that financial firms' positions did not cause the market to expect persistent price increases during 2007/08. Other explanations for the increase in oil prices include macroeconomic fundamentals, such as interest rates and increased demand from emerging Asia. Of these two explanations, the one that seems most consistent with the facts explains oil-price fluctuations in terms of large and persistent demand shocks related to growth in global real activity in the presence of supply constraints.
Keywords: Q41; G12; 330; International topics; Finanzmarkt; Spekulation; Termingeschäft; Erdöl; Zins; Nachfrage; Ölpreis; Welt